Formation of Independent Work Skills for the Purpose of Preparing School Students for CreditModule Education (Journal of Pedagogical Inventions and Practices, 2022)
In this article, the credit-module-based teaching system, in general, education schools, the President of the Republic of Uzbekistan dated August 12, 2020 "On measures to improve the quality of continuous education and the effectiveness of science in the fields of chemistry and biology" No. PQ-4805 the decision and the works carried out within the framework of this decision are discussed.